Spin anisotropy of the resonance in superconducting FeSe0.5Te0.5 - Babkevich, P; Roessli, B; Gvasaliya, SN; Regnault, L; Freeman, P; Pomjakushina, E; Conder, K; Boothroyd, A (2010)
We have used polarized-neutron inelastic scattering to resolve the spin fluctuations in superconducting FeSe0.5Te0.5 into components parallel and perpendicular to the layers. A spin resonance at an energy of 6.5 meV is observed to develop below T_c in both fluctuation components. The resonance peak is anisotropic, with the in-plane component slightly larger than the out-of-plane component. Away from the resonance peak the magnetic fluctuations are isotropic in the energy range studied. The results are consistent with a dominant singlet pairing state with s^{±} symmetry, with a possible minority component of different symmetry.